(untitled) (The New Uzbekistan Journal of Medicine, 2025)
The medical examination of individuals entering into marriage is a crucial factor in ensuring the health and well-being of future generations. In Uzbekistan, where 64% of the population is under 30, early marriage can lead to serious health risks, including infertility, pregnancy complications, and congenital anomalies in newborns. Scientific evidence suggests that men and women achieve full anatomical and physiological maturity after the age of 20, highlighting the importance of delaying marriage until individuals are fully developed. The Cabinet of Ministers’ Decree No. 365 (2003) mandates medical examinations for couples before marriage, aiming to prevent hereditary and infectious diseases and promote the formation of healthy families. The implementation of this law, along with awareness campaigns led by the Scientific and Practical Center "Family" and civil registration offices, has contributed to a significant reduction in the number of children born with congenital anomalies. This study analyzes the results of medical examinations of individuals entering into marriage in Tashkent for the year 2014, assessing the effectiveness of preventive health measures in ensuring family well-being.